Effect of Dzikir (Religious Chanting) Therapy on The Anxiety Level of Third-Trimester Pregnant Women Facing Labor - Dayu Linda Sari; Ana Mariza; Wayan Aryawati; Yuli Yantina (Universitas Malahayati Lampung, 2024)
ABSTRACT Anxiety in the third trimester of pregnancy is often related to impending labor and childbirth. In Indonesia, 28.7% of pregnant women in the third trimester experienced anxiety. The negative impact of anxiety during pregnancy includes the risk of miscarriage and fetal abnormalities. Non-pharmacological therapies based on Islam, such as dzikir (religious chanting) therapy, have been developed. To determine the effect of dzikir (religious chanting) therapy on the anxiety level of third-trimester pregnant women facing labor in the working area of Bandar Negeri Suoh Primary Health Care in the year 2023. This research was quantitative in design and employed a pre-experimental design with a one-group pretest and posttest design. The population of this study consisted of third-trimester pregnant women in the working area of Bandar Negeri Suoh Primary Health Care in July. The total was 35 people, with 30 people as the sample. The sampling technique used is purposive sampling. Moreover, the data analysis involved univariate and bivariate analyses with the Wilcoxon test.The results of this r esearch showed that the average anxiety level of third-trimester pregnant women facing labor before undergoing dzikir (religious chanting) therapy was 21.4, and after undergoing dzikir (religious chanting) therapy, it decreased to 10.7. Bivariate analysis revealed that there was an effect of dzikir (religious chanting) therapy on the anxiety level of third-trimester pregnant women facing labor, with a p-value of 0.000. An effect of dzikir (religious chanting) therapy on the anxiety level of third-trimester pregnant women facing labor in the working area of Bandar Negeri Suoh Primary Health Care in the year 2023. Keywords: Anxiety, The Dzikir (Religious Chanting) Therapy, Pregnant Women